How Long Will It Take to Lift One Billion People Out of Poverty? - Ravallion, Martin (Published by Oxford University Press on behalf of the World Bank, 2015)
Alternative scenarios are considered for reducing by one billion the number of people surviving on less than $1.25 a day. The low-case, “pessimistic” path to that goal envisages the developing world outside China returning to the slower pace of economic growth and poverty reduction of the 1980s and 1990s, but with China maintaining its progress. This path would take 50 years or more to lift one billion people out of poverty. A more optimistic path is identified that would maintain the developing world's (impressive) progress against absolute poverty since the turn of the century. This path would lift one billion people out of poverty by 2025–30. The optimistic path is consistent with both linear projections of the time-series data and nonlinear simulations of inequality-neutral growth for the developing world as a whole.